Teachers’ Understanding Of Block Play Activities For Early Childhood At TK Alam Yaa Bunayya - Nurul Firdausi; Ayunda Sayyidatul Ifadah; Rr. Agustien Lilawati (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study aims to describe teachers’ understanding of block play activities for early childhood at TK Alam Yaa Bunayya. Block play is a learning medium that develops children’s cognitive, motor, socio-emotional, and creative abilities. Its implementation, however, is highly influenced by teachers’ knowledge in designing, guiding, and evaluating play experiences. This research employed a qualitative descriptive approach through observation, interviews, and documentation. The findings reveal that teachers demonstrate a good level of understanding, shown by their ability to apply principles of constructive play, provide appropriate scaffolding, and create safe yet challenging play environments. The study concludes that improving teacher competency is essential to optimize block play as a medium for stimulating children’s holistic development.